ANALISIS PEMAHAMAN KEWANGAN DALAM KALANGAN MAHASISWA AKADEMI PENGAJIAN ISLAM UNIVERSITI MALAYA: Financial Understanding Analysis among Academy of Islamic Studies’ Undergraduates in University of Malaya - Md Sapir, Ana Shakirah; Abdul Halim, Zainul Abidin (Jurnal Syariah, 2020)
With many university students receiving formal financial education, more individual have become significant understanding on their own money management. As a result, they able to successfully manage their own tuition fees, cost of living and entertainment without their parents’ guidance. This paper explored financial understanding of undergraduates at Academy of Islamic Studies University of Malaya (APIUM). Specifically, this paper investigated their demographic profiles and its relationship with their understanding on zakāh, takaful and free-interest loans offered by Islamic financial institutions. In addition, this paper also investigated on their spending behaviour. Characteristics such as field of study, source of education funds, education financing and their spending priority were examined to determine the main drivers behind the receiving of zakāh, subscribing monthly takaful, engaging in interest-based loans as well as their spending behavior. We assumed that financial literacy defined by OECD has become our underlying framework for this paper. Findings indicated that undergraduates with full sponsored by their family have different view about receiving zakāh funds, subscribing takaful, engaging in free-interest loan, and spending on entertainment cost. It is expected that this study would be expanded to more undergraduates who come from rich family backgrounds. It is expected that this study may help university to develop appropriate program of financial education suitable for undergraduates of various demographic profiles including those who come from rich family.